A CRITICAL DISCOURSE ANALYSIS OF SEXISM IN “BRAVE” MOVIE - Robiatul Adawiyah; Elisa Nurul Laili (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Abstract This study focused on describing the sexist language and social structure through movie “ BRAVE " (2012). This article is the result of research qualitative with a desciptive approach of the model Teun-A-Van-Dijk. The results of the study can be formulated that there are two types of sexist language, namely the types of sexist language that are open or direct, namely: naming, dictionary, common pronouns and nouns.Film discourse alone is not enough to rely on text, because it consists of different structures and levels. The structures are macrostructure, superstructure, and microstructure The macrostructure contains the subject structure, the super contains structure the structure schema, and the rest is contained in the microstructure. The two structural elements are true that this film. The film's narrative and language reinforce traditional gender roles and social structures, as shown through the use of Sara Mills and Van Dijk's theories. The research focused the analysis main characters and expressing sexism on “Brave” movie.